PEMILIHAN UMUM MERUPAKAN PERWUJUDAN PELAKSANAAN DEMOKRASI BERDASARKAN UUD NEGARA REPUBLIK INDONESIA TAHUN 1945 - Muzayanah (Jurnal Pengabdian Kepada Masyarakat Media Ganesha FHIS, 2022)
The constitutional system of the Republic of Indonesia is a democratic system, so the highest sovereignty is in the hands of the people, so that the people have the power to determine the election of leaders in the Republic of Indonesia. In 2024, the Government of the Republic of Indonesia has a very important agenda, namely holding General Elections for the President and Vice President. At this time, activities have begun before the general election, including political parties that have registered themselves to take part in the general election later. For this reason, it is necessary to have an understanding of the community about the importance of implementing this general election as a form of embodiment of the implementation of democracy in the administration of the state administration of the Republic of Indonesia. Therefore, it is our obligation, as academics, to carry out and assist the government so that the public will understand the implementation of democracy and carry out general elections with pleasure. For this reason, it is necessary to take steps to provide understanding by providing legal counseling to the community. Considering that the general election is held by voting from the people to choose the presidential and vice presidential candidates promoted by political parties, it is hoped that the citizens will cast their votes in this general election as well as possible. Considering that the right to vote is a human right that must be realized in accordance with the ideals of the Indonesian nation, as referred to in the Pancasila and the 1945 Constitution. For residents of the patients participating in the Prolanis Program at the Pratama Clinic "RAHMATIKA" Gunung Pati, Semarang City, they are Indonesian citizens. who need information and education related to the implementation of the upcoming General Election. For this reason, as the executor of community service activities, he will provide legal counseling related to the general election. Please note that not all residents of Prolanis Clinic Pratama "RAHMATIKA" understand and understand what is meant by Democracy, General Elections and Citizens' Suffrage Rights to carry out general elections. The provisions that form the legal basis for holding General Elections are based on the Election Law and are constitutionally based on the 1945 Constitution. Therefore, it is very important that citizens, in this case the Prolanis Patient, understand and understand and wisely use their right to vote in general elections. the best that will come. This counseling is the responsibility of Academics by carrying out Community Service in implementing Government Programs by providing legal services / counseling to the community to understand and understand that every citizen is guaranteed democratic rights based on the 1945 Constitution.